Pengaruh Fasilitas dan Kualitas Pelayanan Terhadap Kepuasan Tamu di Virgin Villa Ubud - Dewi, Ni Wayan Mery Sintya; Putra, Putu Guntur Pramana; Suryaningsih, Ida Ayu Anggreni (Jurnal Mosaik Hospitaliti, 2025)
Virgin Villa Ubud is one of the private villas in the Ubud area located on Jalan Suweta, Ubud District, Gianyar Regency. The facilities and quality of service provided are important elements that determine guest experience and guest satisfaction. Broadly speaking, measuring guest satisfaction can be done from the assessment of guests who have stayed. Based on the data obtained, it was found that the satisfaction of guests who have stayed at Virgin Villa Ubud can be categorized as still less satisfied with the facilities and quality of service. The facilities available at this villa also require improvements such as the path to the room that becomes slippery during the rainy season, the edge of the swimming pool that needs to be repaired, and the breakfast provided by the villa is less varied in the vegetarian menu. This study aims to determine the effect of facilities and service quality on guest satisfaction. The location of this study was Virgin Villa Ubud. Data collection techniques used were observation, questionnaires and interviews. The population used guests at Virgin Villa Ubud with a sample of 100 respondents. Data analysis techniques used were descriptive statistical analysis, data instrument testing, classical assumptions, multiple linear regression, T- test and F-test of determination. The results of the study indicate that facilities have a positive and significant influence on guest satisfaction, service quality has a positive and significant influence on guest satisfaction, facilities and service quality have a 57.5% influence on guest satisfaction, and service quality has a more dominant influence on guest satisfaction.